TIME CONSUMPTION AND PRODUCTIVITY OF BUCKING OF SENGON IN PRIVATE FORESTS - budiaman, ahmad; Hardjanto; Natalia Rahayaan, Yohana (Jurnal Belantara, 2025)
Bucking is a forest harvesting stage that determines the quality of round wood. The bucking in private forests uses a chainsaw. Efficient bucking process is a prerequisite for sustainable forest harvesting. The study aimed to analyze the working time and productivity of bucking using a chainsaw in private forests. The study was conducted in private forests planted with an agroforestry pattern in the Probolinggo district, East Java. Working time measurements are carried out based on analysis of video images recorded during data collection in the field. The number of bucking work cycles observed was 31 cycles. Regression analysis was used to analyze the relationship between the logs' diameter and length and the bucking's productivity. The average working time for bucking was 7.09 minutes per cycle, consisting of 77.84% working time and 22.16% non-working time. The average productivity of bucking was 2.51 m3/hour. The study provided important empirical results regarding bucking's working time and productivity in private forests where the type of felled tree was sengon. Hopefully, the study results will be useful in planning and developing bucking techniques in private forests in Indonesia.